Sounding queer collaborative acts: Chantal Akerman films Sonia Wieder-Atherton. Issue 3 (1st October 2020) - Fox, Albertine
ABSTRACT: The cellist Sonia Wieder-Atherton has collaborated with Chantal Akerman on her feature films, shorts, documentaries and installations. However, Wieder-Atherton's influence on Akerman's filmmaking, and her physical presence in the films themselves, have not been examined directly by scholars. This article will address this imbalance by outlining their collaborative project, before analysing Akerman's short film Trois Strophes sur le nom de Sacher (1989), in which the cellist performs the eponymous composition by Henri Dutilleux. Through the inter-filmic presence of Alfred Hitchcock's Rear Window (1954) and the allusions to Akerman's Jeanne Dielman (1975), the author argues that the cellist's intense rendering of Dutilleux's score, marked by his use of scordatura, catalyses Akerman's queer mistuning of Hitchcock's classic. In doing so, her film produces a form of ambivalent spectatorship that embraces what the author is calling the 'musically queer'. Her analysis draws on Tania Modleski's critical swerve away from the male gaze in her study of Rear Window, and on Lee Edelman's conceptualisation of Rear Window 's rumbling pulse of anal eroticism. The author will demonstrate how Akerman charges the 'rear view' backdrop of her film with an immersive sonic erotics that decentres the phallocentric scopic regime and fashions an acoustic space for queer spectatorial pleasures.